Learning about Farming: Innovation and Social Networks in a Resettled Community in Brazil - Margherita Comola; Carla Inguaggiato; Mariapia Mendola (Institute of Labor Economics (IZA), 2021)
We study the role of social learning in the diffusion of cash crops in a resettled village economy in northeastern Brazil. We combine detailed geo-coded data on farming plots with dyadic data on social ties among settlers, and we leverage natural exogenous variation in network formation induced by the land occupation movement and the agrarian reform. By using longitudinal data on farming decisions over 15 years we find consistent evidence of significant peer effects in the decision to farm new cash fruits (pineapple and passion fruit). Our results suggest that social diffusion is heterogeneous along observed plot and crop characteristics, i.e. farmers growing water-sensitive crop are more likely to respond to the actions of peers with similar water access conditions.
Keywords: C45; D85; J15; O33; Q15; 330; technology adoption; agrarian reform; social networks; peer effects; Brazil